Multifunctional technology of the "Blurring Borders" project as a driving force for the growth of mass adaptive physical culture and sports - Dubrov A.A.; Karmazinska Yu.O.; Andryushenko L.B.; Glazkova G.B. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The research aims to experimentally confirm the impact of the "Blurring the Lines" Festival on the development of adaptive physical education and improving the quality of life of students in the regions of Russia. Methods and structure of the study. A scientific study was conducted at Plekhanov Russian University of Economics, which included the study of specialized literature, a comparison of the first and second "Blurring the Lines" festivals (2023 and 2024), the definition and explanation of their socio-cultural impact, as well as the development of conclusions and recommendations on the development of adaptive physical culture (AFC) in the regions of Russia. Results and conclusions. Based on the quantitative and qualitative data obtained during the First and Second "Blurring the Lines" festivals, the positive socio-cultural impact of the project on the higher education system in Russia was scientifically substantiated. The festival promotes the development of mass adaptive physical culture by uniting the academic community and improving the socialization of students with special needs. The participation of military veterans, Paralympians and public figures expands the scope and significance of the project. The creation of a digital educational ecosystem provides a platform for the exchange of knowledge and experience. The expert community of the festival proposed scientifically sound measures for the further development of the AFC, including regular scientific and practical conferences and the Universiade "Blurring the Lines", as well as the organization of the III All-Russian Student Festival to promote the health and social adaptation of students.